2016
DOI: 10.1515/jpm-2015-0337
|View full text |Cite
|
Sign up to set email alerts
|

The role of vitamin B1-B2 and plasma lipid profile in intrahepatic cholestasis of pregnancy

Abstract: Increased levels of vitamins B1 and B2 may indicate a need for increased energy metabolism at the fetus. So we believe that new studies are required, which will be supported by the placental analyses of the pyruvate and lactate levels in maternal blood at delivery and fetal cord blood in order to develop a better understanding on the fetal effects of energy metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…It affects~0.3 to 5.6% of pregnancies and has ethnic, geographic, and seasonal variation. 17 China is a high-prevalence area of ICP, where the incidence rate can reach 2.3 to 10.0%, 18 resulting in a great threat to maternal and child health. To the best of our knowledge, only a few studies have reported the association of ICP with abnormal lipid profiles.…”
mentioning
confidence: 99%
“…It affects~0.3 to 5.6% of pregnancies and has ethnic, geographic, and seasonal variation. 17 China is a high-prevalence area of ICP, where the incidence rate can reach 2.3 to 10.0%, 18 resulting in a great threat to maternal and child health. To the best of our knowledge, only a few studies have reported the association of ICP with abnormal lipid profiles.…”
mentioning
confidence: 99%
“…After duplicates were removed, the titles and/or abstracts of the 278 references were carefully screened. After that assessment, 11 studies met the inclusion criteria and were included in the qualitative analysis 11,14–23 . Finally, nine studies were included in the final meta‐analysis, with all nine reporting TG, TC and HDL cholesterol data and eight reporting LDL cholesterol data (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 11 included studies, one was a prospective case–control study 17 and 10 were cohort studies, including seven prospective cohort studies 14,16,18–22 . Study quality was assessed using the modified NOS.…”
Section: Resultsmentioning
confidence: 99%
“…However, abnormal elevations in plasma triacylglycerol levels during pregnancy have been associated with gestational hypertension and preeclampsia, and may be related to preterm births and macrosomic babies ( Vrijkotte et al, 2012 ). In humans, abnormal elevations in triacylglycerol levels during late gestation commonly correlate with excess weight and obesity ( Farias et al, 2016 ), sedentarism ( Monda et al, 2009 ), smoking ( Gastaldelli et al, 2010 ), vitamin D deficiency ( Başaranoğlu et al, 2017 ), and use of some medications (i.e., beta blockers, valproate, and sertraline; Wild et al, 2016 ) in mothers.…”
Section: Introductionmentioning
confidence: 99%